Developing covid-19 web and mobile web situation reporting applications for the state health authority - Iza Azura Ahmad Bahar; Suddin Lada; Nona Masnie Mohd. Nistah; Syed Nasirin Syed Zainol Abidin; Esmadi Abu Abu Sema; Suraya Miskon (Institute of Electrical and Electronics Engineers, 2021)
If Malaysia ends up entering the subsequent COVID-19 outbreak, many hospitals will no longer support the victims conveniently. There will be numerous victims around, and these hospitals will not have enough human resources. Exceptional ICT-based communication backbone should also be in place to fully recommend these hospitals day-to-day operations. For this reason, COVID-19 situational reporting web and mobile web applications were developed to assist the health professionals in the State of Sabah in doing their job with a high level of assurance. Several real-time technologies were put together as the foundation in developing these applications. This work-in-progress paper presents the design and development techniques employed in rapidly developing the COVID-19 situational reporting web and mobile web applications for State Health Authority of Sabah.